Lighting spectra for the maximum colorfulness - Masuda, Osamu (2011)
The advent of modern solid-state sources enabled almost any spectrum for lighting and a wide range of possibilities in color rendering. The quality of the lighting has been typically evaluated by the color rendering index which measures how much the colors of objects illuminated by the light under test look similar to those produced when the objects are illuminated by the daylight or a conventional incandescent light. On the other hand, how colorful or vivid the colors under the illumination are perceived is also an important quality to evaluate lighting. We investigated, computationally, the spectral profiles of the illumination that maximizes the theoretical limit of the perceivable object colors. A large number of metamers with various degree of smoothness were generated using the Schmitt’s elements method at chromaticity points on and around the Planckian locus ranging from 2,222 K to 20,000 K. The general color rendering index (CRI) and MacAdam volumes in CIELAB color space were calculated for each metamer. The metamers maximizing the CRI had smoother spectra than the metamers maximizing the MacAdam volume. These results show that maximum colorfulness in nature can only be obtained with spectrally non-smooth illumination